Assessment of the feed additive consisting of Pediococcus pentosaceus DSM 14021 for all animal species for the renewal of its authorisation (Chr. Hansen A/S) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of Pediococcus pentosaceus DSM 14021, a technological additive for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. The Panel concluded that the additive remains safe for all animal species, consumers and the environment under the authorised conditions of use. Regarding user safety, the Panel considers that any exposure through skin and respiratory tract is considered a risk. The Panel cannot conclude on the eye irritation potential of the additive due to the lack of data. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.